(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Board characteristics and its impact on performance of the banks has been an area of attraction for researchers since last two decades. The present study focuses on measuring the impact of board characteristics on financial performance of Indian banks. The database of 35 Scheduled Commercial listed banks operating in India including 18 public and 17 private sector banks have been analyzed for a period of 7 years i.e. from 2012-13 to the year 2018-19. A standard method of calculating heteroscedasticity- robust standard error for the fixed effect model and clustered standard error regression technique was used to address the problem of serial correlation consistent with fixed effect estimator. Financial performance is measured using ROA and ROE. It is concluded that the board independence and number of board meetings are significantly and negatively associated with return on asset. However, Board size is positively and significantly associated with ROE.